Corrosion in Dental Implant - Navasri, Chutima; Khemthong, Kantika; Angkasith, Pattarika; Chaijareenont, Pisaisit (Srinakharinwirot University Dental Journal (E-ISSN 2774-0811), 2022)
At the present, dental implants have become a part of dental treatment to replace missingteeth. Dental implants are mainly made of titanium or its alloy because of proper physical, chemical,and biological properties that provide a high resistance to corrosion due to protective surfacetitanium dioxide layer. However, the titanium dioxide layer can be damaged when dental implantscontact with metal implant abutment and prosthesis in oral environment for a long period of timewhich leads to corrosion in dental implant. Corrosion could be influenced by various factors, includingmicroorganisms around dental implant, acidic environment from food or chemical agents, and metalusage with electric potential difference may influence corrosion. Metallic particles released from corrosion affect various aspects such as clinical symptoms,tissue pigmentation, cellular response leading to bone loss, and delayed fracture of dental implant.Therefore, properly chosen metal alloy for implant abutment and dental crown altogether with pHcontrol in oral environment are the important factors to decrease corrosion of dental implants. Keywords: Biocompatibility, Corrosion, Dental implants corrosion, Titanium SWU Dent J. 2022;15(1):108-23.